Grain boundary mediated plasticity: The role of grain boundary atomic structure and thermal activation. (1st March 2018) - Terentyev, D.; Bakaev, A.; Serra, A.; Pavia, F.; Baker, K.L.; Anento, N.
Abstract: The interaction of dislocation pile-ups with several tilt grain boundaries (GB) is studied in copper by using a hybrid continuum-atomistic approach. The effects of temperature, pile-up intensity and GB structure on absorption and transmission of slip as a function of local stress state are explored. By considering several high-angle GBs with different misorientation angles, we demonstrate that GB atomic structure primarily defines its ability to accommodate incoming pile-up dislocations, thus limiting the direct transmission of pile-ups through the interface. Graphical abstract: We have developed an efficient computational model based on the combination of MD and mean-field approached (driven by linear elasticity theory) to investigate the full atom-scale details of the interaction of dislocation pile-ups with grain boundary interface in FCC copper. The local stress, acting on the leading dislocation interaction with the GB, and overall resolved shear stress was calculated to provide quantitative figures characterizing the Dislocation-GB slip transfer phenomenon. It is demonstrated that the GB core structure primarily defines its ability to accommodate incoming pile-up dislocations on the GB interface. Dynamic dislocation re-arrangement prevents accumulation of stress-concentration at the intersection of pile-up and GB interface. In the highly disordered GBs, where slip is totally suppressed, the conditions for the dislocation transmission are deduced. The obtained results are summarised to provide quantitative basis for the implementation of the Dislo-GB interaction rules in up-scale models such crystal plasticity and finite elements.